Incidence of subclinical endometritis and its effects on reproductive performance of crossbred dairy cows - Carneiro, Luisa Cunha [UNESP]; Ferreira, Adolfo Firmo; Padua, Mariana; Saut, Joao Paulo; Ferraudo, Antonio Sergio [UNESP]; Santos, Ricarda Maria dos (Springer, 2014)
In dairy cattle, uterine infections are not life threatening and often unavoidable; however, they reduce fertility and increase the production costs of properties. The aim of this study was to evaluate the incidence of subclinical endometritis from 32 to 70 days in milk (DIM) and its effects on the reproductive performance of crossbred dairy cows. Lactating cows (Holstein/Gir; n = 172), with no history of retained placenta, without clinical signs of uterine infection were used. The body condition score (BCS) was evaluated on a scale from 1 to 5. Ultrasound examination was performed to evaluate uterine lining and ovarian activity, while vaginal mucus was analyzed by gloved hand. The diagnosis of subclinical endometritis was performed by endometrial cytobrush technique. The samples were collected, stained, and examined microscopically; positive cases for subclinical endometritis were considered with the presence of a parts per thousand yen5 % of neutrophils. Later, the cows were submitted to conventional artificial insemination or timed artificial insemination. The incidence of subclinical endometritis in the herd was 26 %, and this was not affected by the season of calving, presence of corpus luteum, DIM, and parity. Cows with a BCS a parts per thousand currency sign2.50 had a higher incidence of subclinical endometritis. The conception rate to first insemination and pregnancy rate at 150 days postpartum were not influenced by the presence of subclinical endometritis in crossbred dairy cows.
Keywords: Cytobrush; Neutrophils; Uterine infection; Reproduction